Exploring pathways leading to stillbirths and gaps in postnatal care among affected women in a rural north Indian district: A qualitative study using the social autopsy lens - Barsha Gadapani Pathak; Sonia Maurya; Shruti Bisht; Pranay Vats; Reema Mukerjee; Vinod Kumar Anand; Sarmila Mazumder (PLoS ONE, 2026)
Background Globally, stillbirth is a silent yet significant contributor to perinatal mortality. India has several national maternal and child health programs, yet, the stillbirths remain poorly reviewed, subject to suboptimal surveillance, are under-reported, and often absent from many programmatic priorities. This study aimed to explore the pathways, delays leading to stillbirths and continuum of care in postpartum phase among affected women in a rural district of North India using a social autopsy tool. Methods This qualitative study was a component of an ongoing implementation research to reduce stillbirth in Palwal district of Haryana. In-depth interviews were conducted with 25 women who had experienced stillbirths using a specially designed social autopsy tool. Additionally, five healthcare providers were interviewed for getting a holistic insight on pathway leading to stillbirth. Thematic analysis was performed using NVivo 16 software, and both deductive (Three Delays Model framework) and inductive approaches were applied to identify delays and contextual factors influencing care-seeking, and postpartum experiences. Results The pathways identified as contributor stillbirths were: (i) low utilization of antenatal and delivery care, driven by cultural beliefs, low perceived risk, and gendered power dynamics; (ii) delays in accessing care due to poor transport, restrictive social norms, and infrastructural gaps; (iii) poor quality of care, characterized by disrespectful treatment, inappropriate referrals, and inadequate intrapartum management. Additionally, a complete absence of postpartum follow-up, grief support, or mental health care was found, reflecting a neglected dimension of postpartum maternal care following stillbirths. Conclusions Stillbirths in this setting are the consequence of interlinked socio-cultural, health system, and gendered vulnerabilities. The implications of stillbirths extended beyond immediate consequences to include enduring mental health and social impacts, ultimately undermining women’s confidence, well-being and preparedness for future pregnancies. There is an urgent need to integrate stillbirth reporting, respectful maternity care, and post-loss psychosocial support within India’s maternal health programs. Trial Registration The primary implementation research was registered prospectively in the Clinical Trial Registry of India (CTRI): CTRI/2024/07/069796 [ Registered on: 02/07/2024 ].